2022
DOI: 10.1111/nmo.14495
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antegrade enema initiation on healthcare utilization in pediatric patients: A population‐based cohort study

Abstract: Background When constipation is refractory to first‐line interventions, antegrade enema use may be considered. We aimed to assess the impact of this intervention on healthcare utilization. Methods We conducted a population‐based, quasi‐experimental study with pre–post comparison of the intervention group and a non‐equivalent control group using linked clinical and health administrative data from Ontario, Canada. Subjects included children (0–18 years) who underwent antegrade enema initiation from 2007 to 2020 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Medical risks include stoma break down, stomal stenosis, pain with enema, increased risk of infection, and potential surgical revisions 18–20 . Relatedly, patients who undergo ACE have demonstrated increased emergency department visits compared to controls 21 . Additionally, the regimen following surgery requires daily flushes and toilet sits for extended periods of time (e.g., 45 min) which may be taxing on families and may also be difficult for children and adolescents to complete.…”
Section: Antegrade Continence Enema In Pediatric Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical risks include stoma break down, stomal stenosis, pain with enema, increased risk of infection, and potential surgical revisions 18–20 . Relatedly, patients who undergo ACE have demonstrated increased emergency department visits compared to controls 21 . Additionally, the regimen following surgery requires daily flushes and toilet sits for extended periods of time (e.g., 45 min) which may be taxing on families and may also be difficult for children and adolescents to complete.…”
Section: Antegrade Continence Enema In Pediatric Patientsmentioning
confidence: 99%
“…[18][19][20] Relatedly, patients who undergo ACE have demonstrated increased emergency department visits compared to controls. 21 Additionally, the regimen following surgery requires daily flushes and toilet sits for extended periods of time (e.g., 45 min) which may be taxing on families and may also be difficult for children and adolescents to complete. One study noted that several families reported their child resented the time that was required to complete daily flushes.…”
Section: Key Pointsmentioning
confidence: 99%